Discounts and Services on Ticket Sales for the Badminton Indonesia Open Tournament on Customer Satisfaction. Issue 1 (27th August 2020) - Putro, Abraham Abimanyu Kristiyono; Adam, Mohamad; Hudri, Alman; Widiyanti, Marlina
No abstract available